KESIAPAN APARAT BIROKRASI MENUJU PARADIGMA GLOBAL PELAYANAN PUBLIK - Bambang Wicaksono (Populasi, 2002)
The issue of public service provision has become more serious in Indonesia in line with increasing public awareness of the need for customer-oriented public service delivery. The institutional capacity preparations and good quality human resources within the bureaucracy confines should back up endeavors in the direction of instituting a new public service delivery paradigm, which among other things, should uphold the sovereignty of the user. Bureaucracy, as a public service institution, must be equipped with the ability to adopt the concept of an adaptive organization, which is a public service delivery institution always sensitive to any changes in the needs and environment of service users the people.